Combined Diagnostic Significance of Preoperative Serum β2-Microglobulin and Routine Blood Test in Patients with High-grade Glioma and Solitary Brain Metastasis - Li L; Bu X; Wu B; Zhang S; Jin K; Xia L; Sun C (Cancer Management and Research, 2020)
Liwen Li,1,* Xiaomin Bu,2,* Bin Wu,1 Shuyuan Zhang,1 Kai Jin,1 Liang Xia,1 Caixing Sun1 1Department of Neurosurgery, Cancer Hospital of the University of Chinese Academy of Sciences (Zhejiang Cancer Hospital), Institute of Basic Medicine and Cancer (IBMC), Chinese Academy of Sciences, Hangzhou, Zhejiang 310022, People’s Republic of China; 2Department of Clinical Laboratory, Cancer Hospital of the University of Chinese Academy of Sciences (Zhejiang Cancer Hospital), Institute of Basic Medicine and Cancer (IBMC), Chinese Academy of Sciences, Hangzhou, Zhejiang 310022, People’s Republic of China*These authors contributed equally to this workCorrespondence: Caixing Sun; Liang Xia Tel +86-571-88122222; Tel +86-13777820122Email 2226124552@qq.com; 350641012@qq.comBackground: High-grade glioma (HGG) and solitary brain metastasis (sBM) patients show similar symptoms in clinical practice, and accurately differential diagnosis directly affects the management and prognosis of patients. The aim of this study was to distinguish two entities by preoperative serum β 2-microglobulin (β 2-m) and routine blood test-associated inflammatory indexes including, white blood cell (WBC), neutrophils, lymphocytes, monocytes, and platelets count, red cell distribution width (RDW), platelet distribution width (PDW), neutrophil/lymphocyte ratio (NLR) and monocyte/lymphocyte ratio (MLR).Patients and Methods: A retrospective analysis was performed in the Cancer Hospital of the University of Chinese Academy of Sciences from January 2015 to December 2019, including 127 patients of newly pathologically diagnosed with HGG and 174 patients with sBM. Clinical information including age, gender, pathological diagnosis, preoperative serum β 2-m and routine blood tests were collected, and NLR and MLR were calculated. The diagnostic significance of these markers for HGG and sBM was assessed by receiver operating characteristic (ROC) curves.Results: The patients with sBM had significantly higher values of preoperative age, β 2-m, NLR and MLR as well as lower lymphocytes count than patients with HGG. Besides, the area under the curve (AUC) in differentiating HGG from sBM was 0.625 (95%CI: 0.561– 0.689) for age, 0.655 (0.594– 0.717) for β 2-m, 0.634 (0.571– 0.698) for NLR and 0.622 (0.559– 0.686) for MLR, and the combination of Age+β 2-m+NLR+MLR showed the best diagnostic performance with AUC of 0.731 (0.675– 0.788) and 0.048*Age+0.001*β 2-m+0.201*NLR+0.594*MLR> 5.813 could indicate sBM rather than HGG.Conclusion: The Age+β 2-m+NLR+MLR combination was revealed as an inexpensive and noninvasive biomarker for differentiating between HGG and sBM before surgery.Keywords: solitary brain metastasis, β 2-microglobulin, neutrophil/lymphocyte ratio, monocyte/lymphocyte ratio, routine blood test, high-grade glioma